To study the commercial and operational advantages and disadvantages of mega-container ships (>14,000TEU) - Lai, Marie Jinbao (2014)
Containerised trade has been expanding over the years. In order to bring down the per-unit cost of transporting the containers, many shipping lines have began to order container vessels with increased container carrying capacity. They did that is to take advantage of the economies of scale that mega-container vessels can bring.